Application of different calibration methods for the Hargreaves-Samani model in Southeast Brazil (Research, Society and Development, 2020)
The evapotranspiration is an important variable in the hydrological cycle and one of the main components of water balance in the soil. The use of simplified equations is a potential alternative to estimate reference evapotranspiration (ET0) when there is limited meteorological data. The objective of this study was to test different methods to estimate ET0 using the Hargreaves-Samani equation (HS) under different meteorological conditions. ET0 was calibrated with HS, adjusting the HS coefficient (HC), using different methods. Adjustment by linear regression was also performed. ET0 was also estimated using the original HS and Penman-Monteith FAO-56 methods with limited climatic data (PML). The performance of the methods (mean absolute error, mm day-1) to estimate evapotranspiration, based on Penman-Monteith, were: PML (1.46); HS (0.68); Vanderlinden et al. (2004) (0.81); Martí et al. (2015) (0.77); and linear regression (0.53). The PML method presented the worst performance. Adjustment by linear regression presented a better performance than the adjustments of HC, improving the ET0 estimates by up to 30%, and it is considered the most recommendable of the methods tested.